Pengaruh Terapi Sosiodrama terhadap Peningkatan Perilaku Prososial pada Siswa Pondok Pesantren Al-Malul Khair Palembang - Shintia Miwiapi; Sarah Afifah (Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2021)
This study aims to determine the effect of sociodrama therapy on increasing prosocial behavior in students of Al- Amalul Khair Islamic boarding school Palembang.The research method used is a quasi-experimental research design with non-equivalent control group design. The sample used was not chosen randomly.The sample used was the seventh grade students of the Al-Amalul Khair Islamic boarding school, Palembang, which was divided into two groups, namely 10 experimental groups and 10 control groups.The research instrument used was a prosocial behavior scale which was analyzed using an independent sample T-test with the help of SPSS (Statistics Program for Social Science) version 26 for windows. the results of the prosocial behavior scale study obtained the value of t count (3.970)> t table (2.101), then Ho is rejected and (2-tailed) (0,001)<(0,05), Ho is rejected and Ha is accepted. Based on the results of the research conducted, it was concluded that sociodrama therapy had an effect on increasing prosocial behavior of students at the Al Amalul Khair Islamic boarding school in Palembang.